An artificial triazole backbone linkage provides a split-and-click strategy to bioactive chemically modified CRISPR sgRNA - Lapatrada Taemaitree (Nature Portfolio, 2019)
For CRISPR-Cas9 genome editing, Cas9 protein is guided to its target by single guide (sg) RNA. Here, the authors synthesised sgRNAs via convergent ‘click’ ligation of variable 20-mer RNAs that target the genome and a Cas9-binding 79-mer chimeric RNA/2´-OMe RNA of fixed sequence in a single tube.